Mejora de la capacidad portante de la subrasante aplicando cal en vías de segundo orden del cantón Alausí. - Yunga Silva, Alexander Santiago (2023)
Most of the country's road structure is not in good condition, either due to lack of maintenance, and few roads considered first order. In the Alausí canton, most of the roads are second or third order, which is why they are ballasted and should be kept in good condition, but due to the little study of the soil at the time of construction, premature wear occurs, considerably reducing their useful life. and the lack of budget means that their respective maintenance is not carried out. It is for this reason that an alternative proposed with which it is to optimize the resources for its improvement of useful life, where lime is used in the subgrade to improve its bearing capacity. For this, the study of the second order road Sibambe-Multitud de Alausí of 48.5 km was carried out, in which 3 relevant strata obtained and with it the study of its characteristics and in turn obtaining its bearing capacity by adding quicklime in a 2%, 4% and 6% to obtain the optimal percentage for its placement in the subgrade. Favorable results obtained in which stratum 2 improved with 2% lime by 1.94% compared to the natural soil, with 6% lime an improvement of 148.27% obtained. In stratum 3 at 2% lime an improvement of 9.6% obtained, at 4% lime an improvement of 203.12% obtained. In stratum 4, 354.08% improvement obtained at 2% lime and 631.16% obtained at 4% lime, concluding that 4% lime is the optimal amount of placement in those strata for improvement, being a reduction considerable investment and optimizing the amount of lime.